Not Too Involved but Really Care: Father’s Acceptance Who Have Children with Autism Spectrum Disorder (ASD) - Nailul Fauziah; Suryanto Suryanto; Endang Sri Indrawati (Journal of Educational, Health and Community Psychology, 2024)
ASD constitutes a persistent mental disorder that significantly impacts family dynamics, involving both parents and siblings. Limited research has delved into the dynamics of how siblings undergo the process of accepting a father with an ASD child. This study aims to investigate the unique process of paternal acceptance in the context of children with ASD. Utilizing a case study approach, in-depth interviews will be conducted with 8 fathers of ASD children. The acceptance journey for fathers in the realm of ASD differs from the stages outlined in Ross' theory. Fathers traverse a stage of confusion followed by the realistic stage, contemplating the subsequent steps and actions to optimize the development of their ASD children. While fathers may not be directly involved in day-to-day parenting tasks, they exhibit commitment by providing financial support, monitoring their children's ASD development, and realistically preparing for their future.